Pengetahuan gizi, pola asuh, dan asupan makanan dengan status gizi bayi dan balita - Citra Indah Sari; Fika Minata Wathan; Eka Rahmawati; Titin Dewi Sartika Silaban (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Nutritional status is a balance between nutrient intake from food and the nutritional requirements needed for body metabolism. WHO 2018 stated that in 2017 around 7.5% or 50.5 million children under five experienced malnutrition which resulted in failure to grow and develop.Purpose: To determine the relationship: its nutritional knowledge, parenting, and food intake with the nutritional status of infants and toddlersMethod: The quantitative study with a cross-sectional approach, was done in January-February 2022 in Tanjung Ning Lama village. The population in this study were mothers who had infants or toddlers with a sample of 83 respondents who were taken by simple random sampling technique. The results of the analysis used statistical tests, namely the chi-square test to see the univariate and bivariate analysis.Results: Show that the knowledge of nutrition was good 57 respondents with a percentage of 68.7%, good food intake 53 respondents with a percentage of 63.9%, poor parenting 47 respondents with a percentage of 56.6%, and good nutritional status 52 respondents with a percentage of 62.7%. While the results of the bivariate analysis of maternal knowledge were good 80.8% (p-value = 0.005, OR: 4.480), good food intake 75% (p-value = 0.012. OR: 1.415), bad parenting 74.2% (p-value = 0.012).= 0.012 and OR: 3.354) that there is a partial relationship with the nutritional status of toddlers and infants.Conclusion: There is a relationship between maternal knowledge, food intake, and parenting simultaneously with the nutritional status of infants and toddlers.Keywords: Knowledge; Food intake; Parenting; Nutritional Status of Infants and Toddlers. Pendahuluan: Status gizi adalah keseimbangan antara asupan zat gizi dari makanan dengan kebutuhan zat gizi yang diperlukan untuk metabolisme tubuh. WHO 2018 menyatakan pada tahun 2017 di dunia sekitar 7,5% atau 50,5 juta balita mengalami gizi kurang yang berdampak gagal tumbuh kembang.Tujuan: Untuk mengetahui hubungan: pengetahuan gizi, pola asuh, dan asupan makanan dengan status gizi bayi dan balitaMetode: Penelitian kuantitatif dengan pendekatan cross sectional, dilakukan pada bulan Januari-Februari 2022 di desa Tanjung Ning Lama. Populasi dalam penelitian ini adalah ibu yang memiliki bayi atau balita dengan sampel sebanyak 83 responden yang diambil dengan teknik simple random sampling. Hasil analisis menggunakan uji statistik yaitu uji chi-square untuk melihat analisis univariat dan bivariat.Hasil: Menunjukkan pengetahuan gizi baik 57 responden dengan persentase 68,7%, asupan makanan baik 53 responden dengan persentase 63,9%, pola asuh kurang baik 47 responden dengan persentase 56,6%, dan status gizi baik 52 responden dengan persentase 62,7%. Sedangkan hasil analisis bivariat pengetahuan ibu baik 80,8% (p-value = 0,005, OR: 4,480), asupan makanan baik 75% (p-value = 0,012. OR: 1,415), pola asuh buruk 74,2% (p-value = 0,012. OR: 1,415), pola asuh buruk 74,2% (p- nilai = 0,012 dan OR: 3,354) bahwa ada hubungan parsial dengan status gizi balita dan bayi.Simpulan: Ada hubungan antara pengetahuan ibu, asupan makanan, dan pola asuh secara simultan dengan status gizi bayi dan balita.